Saunders nursing drug handbook 2014 - Hodgson, Barbara B.; Kizior, Robert J. (Elsevier, 2014)
"Written by two expert nursing and pharmacy clinicians and organized alphabetically by generic drug name, Saunders Nursing Drug Handbook 2014 provides essential information for over 1,000 generic name and 4,000 trade name drugs in one quick, convenient source. With comprehensive coverage of IV drug administration as well as guidance through clinical priorities in the practice setting, this resource offers the precautionary information you need to provide safer patient care."-- From publisher's description